Student evaluations of teaching in business and accounting courses: A perspective and a suggested improvement - Mitchell Franklin (Taylor & Francis Group, 2016)
Student evaluations of teaching can play a significant role on how one is perceived as a college instructor. In the case of many colleges and universities, the student evaluation is the primary measure used in decisions such as promotion and tenure, or contract renewal of the non-tenure track faculty. The accuracy of student evaluations of teaching is a very heavily researched area. Though many elements such as influence of grade and rigor on student perception have been highly mixed as to impact on student evaluation, there are many other variables that have been clearly shown to strongly influence student perceptions in the evaluation of a faculty member. This paper reviews several pieces of research to clearly show that evaluations can be biased, and suggests an alternate approach to the evaluation of teaching that contains a mixture of student evaluation in a less biased manner, blind peer review of instructional materials by a credentialed faculty member and in class observation by peers or administrators. This paper does not show that a peer-review method is indeed more effective, but suggests that programs consider whether or not a peer review of teaching, or similar method of evaluation can be more effective within their respective programs.